Conservation and conventional vegetable cultivation increase soil organic matter and nutrients in the Ethiopian highlands - Belay, S. A.; Assefa, T. T.; Worqlul, A. W.; Steenhuis, T. S.; Schmitter, Petra S.; Reyes, M.R.; Prasad, P.V.V.; Tilahun, Seifu A. (MDPI, 2022)
Agriculture in Africa is adversely affected by the loss of soil fertility. Conservation agriculture (CA) was introduced to curb the loss of soil fertility and water shortages and improve crop productivity. However, information on how CA practices enhance soil quality and nutrients is scarce in the sub-Saharan Africa context. The objective of this study was to investigate the effects of CA and conventional tillage (CT) on soil organic matter and nutrients under irrigated and rainfed vegetable on-farm production systems. During the dry and wet monsoon phases in the northern Ethiopian Highlands, a four-year experiment with CA and CT was carried out on ten vegetable farms under rainfed and irrigated conditions. Although the increase in concentration of organic matter in CA was generally slightly greater than in CT, the difference was not significant. The average organic matter content in the top 30 cm for both treatments increased significantly by 0.5% a-1 from 3% to almost 5%. The increase was not significant for the 30–60 cm depth. The total nitrogen and available phosphorus concentrations increased proportionally to the organic matter content. Consequently, the extended growing season, applying fertilizers and livestock manure, and not removing the crop residue increased the nutrient content in both CA and CT. The increase in CA was slightly greater because the soil was not tilled, and hay was applied as a surface cover. Although CA increased soil fertility, widespread adoption will depend on socioeconomic factors that determine hay availability as a soil cover relative to other competitive uses.